2007
DOI: 10.1177/0363546506295178
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Prolonged Fresh Osteochondral Allograft Transplantation of the Femoral Condyle

Abstract: Prolonged fresh allograft transplantation is a safe and effective technique for addressing symptomatic osteoarticular lesions in the knees of young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 67 publications
10
161
0
2
Order By: Relevance
“…It still remains unclear how fresh-stored graft compares with slow-freezing cryopreserved grafts, which still have some chondrocyte viability [32,50]. In addition, recent clinical studies with fresh-stored allograft with prolonged storage time report good outcomes, which also supports the notion that there may be a critical minimum number of functioning chondrocytes that can maintain the extracellular matrix [22,45,64].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It still remains unclear how fresh-stored graft compares with slow-freezing cryopreserved grafts, which still have some chondrocyte viability [32,50]. In addition, recent clinical studies with fresh-stored allograft with prolonged storage time report good outcomes, which also supports the notion that there may be a critical minimum number of functioning chondrocytes that can maintain the extracellular matrix [22,45,64].…”
Section: Discussionmentioning
confidence: 94%
“…First, we used an ovine animal model, which has limited extrapolations to humans. However, recently published clinical reports on the effect of cold storage on human osteochondral plugs appear to demonstrate a comparable effect on human tissue with cold storage [22,45,64]. Second, in our protocol, storage was in a nutritive medium that was changed sterilely every 48 hours as previously described [65].…”
Section: Discussionmentioning
confidence: 99%
“…A 96% survival rate was shown by McCulloch et al (18) in a study of 25 consecutive patients treated for lesions of the femoral condyle, with minimum follow-up of two years. LaPrade et al (15) showed good clinical results for the FOAT stored for between 15 and 28 days after procurement, with a mean follow-up time of three years.…”
Section: Clinical Evidencementioning
confidence: 85%
“…Due to the need to prepare cultures for viruses and bacteria in the donor and in the organs, the osteochondral tissue is generally stored for longer, and released at least 14 days after procurement (17 . McCulloch et al (18) and Williams et al (19) demonstrated good clinical results in the fresh transplant performed at up to 42 days of refrigeration. Frozen osteochondral tissues can be used in surgical procedures; however, there is a higher likelihood of delamination, fissures, and failure and collapse of the chondral surface (20,21) .…”
Section: Basic Sciencementioning
confidence: 99%
“…McCulloch et al (45) published a series of 25 cases of patients with osteochondral lesions who underwent allogenic osteochondral transplantation, with a twoyear follow-up. They found statistically significant improvements in the Lysholm, IKDC, KOOS and other scores; 84% of the patients were satisfied with the results and rated the functionality of the operated knee as 79%, in relation to the non-operated knee.…”
Section: Allogenic Osteochondral Transplantationmentioning
confidence: 99%